2002
DOI: 10.1046/j.1440-1746.17.s3.30.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbal medicines for liver diseases in India

Abstract: The use of natural remedies for the treatment of liver diseases has a long history, starting with the Ayurvedhic treatment, and extending to the Chinese, European and other systems of traditional medicines. The 21st century has seen a paradigm shift towards therapeutic evaluation of herbal products in liver diseases by carefully synergizing the strengths of the traditional systems of medicine with that of the modern concept of evidence-based medicinal evaluation, standardization of herbal products and randomiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 28 publications
1
71
0
1
Order By: Relevance
“…Melting points were determined with a Kofler hotstage apparatus. 1 H NMR spectra were run in CDCl 3 on a Bruker Avance-400 spectrometer using Me 4 Si as an internal standard. For analytic and preparative use, TLC plates were spread with Silica Gel 60 GF (Merck).…”
Section: Cell Linesmentioning
confidence: 99%
“…Melting points were determined with a Kofler hotstage apparatus. 1 H NMR spectra were run in CDCl 3 on a Bruker Avance-400 spectrometer using Me 4 Si as an internal standard. For analytic and preparative use, TLC plates were spread with Silica Gel 60 GF (Merck).…”
Section: Cell Linesmentioning
confidence: 99%
“…Thyagarajan et al [41], proved that Milk Thistle act as anti-oxidative, antilipidperoxidative, antifibrotic, anti-inflammatory, immunomodulating and liver regenerative. Extensive studies on Phyllanthus A confirmed that this plant being anti-viral against HBV and HVC, hepatoprotective and immunomodulator, and antiinflammatory properties.…”
Section: Discussionmentioning
confidence: 99%
“…Chinese herbs are Yinchen, Huanggi, and Gancho with pluak rak mon (part of the mulberry root) and Dok kham foi (extracted from safflowers) [33]. Silybim marianum (milk thistle), Glycyrrhiza glabra, Picrorhiza kurroa, and Phyllanthus amarus are confirmed as safe and hepatoprotective herbals used for repairing liver function, [55]. Orange juice is considered as a rich dietary source of antioxidants for patients with hepatitis C under antiviral therapy [56].…”
Section: Medicinal Plants In Avrtmentioning
confidence: 99%